Association of polymicrobial interactions with dental caries development and prevention - Zhu, Yimei; Wang, Ying; Zhang, Shuyang; Li, Jiaxuan; Li, Xin; Ying, Yuanyuan; Yuan, Jinna; Chen, Keda; Deng, Shuli; Wang, Qingjing (Frontiers in Microbiology, 2023)
Dental caries is a common oral disease. In many cases, disruption of the ecological balance of the oral cavity can result in the occurrence of dental caries. There are many cariogenic microbiota and factors, and their identification allows us to take corresponding prevention and control measures. With the development of microbiology, the caries-causing bacteria have evolved from the traditional single Streptococcus mutans to the discovery of oral symbiotic bacteria. Thus it is necessary to systematically organized the association of polymicrobial interactions with dental caries development. In terms of ecology, caries occurs due to an ecological imbalance of the microbiota, caused by the growth and reproduction of cariogenic microbiota due to external factors or the disruption of homeostasis by one's own factors. To reduce the occurrence of dental caries effectively, and considering the latest scientific viewpoints, caries may be viewed from the perspective of ecology, and preventive measures can be taken; hence, this article systematically summarizes the prevention and treatment of dental caries from the aspects of ecological perspectives, in particular the ecological biofilm formation, bacterial quorum sensing, the main cariogenic microbiota, and preventive measures.